PENGARUH KELENGKAPAN PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN (Studi pada Konsumen Toko Bazar Bangunan Tambun Bekasi) - Muhammad Hamzah Ramazan (Laboratorium FEBI UIN SGD Bandung, 2024)
This study aims to determine the partial and simultaneous effect of Product Completeness and Promotion on Consumer Purchase Decisions at the Toko Bazar Bangunan Tambun Bekasi. The research method used is descriptive and verification research methods with a quantitative approach. Data analysis techniques using Descriptive Analysis, Validity Test, Reliability Test, Multiple Linear Regression Test, t-test (partial), F-test (simultaneous), and Coefficient of Determination Test using SPSS version 27. Based on the results it shows that Product Completeness has an effect positive and significant effect on Purchase Decisions and Promotions have a positive and significant effect on Purchase Decisions and simultaneously Completeness of Products and promotions have a significant effect on Purchase Decisions as evidenced by the value of Fcount > Ftable which is 563.221> 3.10, when referring to the test of the coefficient of determination of 0.924 or 92.4% and 7.6% were influenced by other factors that were not investigated by the researchers. Thus, the relationship between the variables in this study has a very strong level of relationship.